Development of innovative marketing technologies in the field of tourism - Basov, Dmitriy; Sokyrko, Vitaliy; Pererva, P. G. (Полтавський державний аграрний університет, 2023)
The use of the proposed advertising schedule in combination with the formation of demand and sales promotion will allow the tourist enterprise to obtain a synergistic effect, that is, each element of promotion will complement the previous ones and strengthen the overall effect on the consumer.
Розвиток інноваційних технологій маркетингу у сфері туризму
Keywords: tourism business; enterprises; marketing; partners; services